Determinants of becoming an M&A acquirer or target: Evidence from the US insurance industry - Gökhan Özer; Nurullah Okur; İlhan Çam (Journal of Capital Markets Studies (JCMS), 2022)
Purpose This paper explores which fundamental aspects of US insurance firms are significant factors in determining whether a firm will be a target or acquirer firm. Design/methodology/approach By focusing on 251 mergers and acquisitions (M&A) deals (119 target firms and 132 acquirer firms) over the period between 1990 and 2019, multinomial logistic regression results identify the determinants associated with becoming targets or acquirers. Findings US insurance firms are more likely to become targets if they are smaller, have lower cash holdings, are non-life, and do not have environmental, social and governance (ESG) scores. Insurance firms are more likely to be acquirers if they have higher profitability, higher cash flow and higher intangibles, and if they are non-life and do not have ESG scores. Moreover, the likelihood of becoming an acquirer decreases in times of global financial crises (GFCs) as compared to non-GFC times. Originality/value This paper is the first to utilize multi-period multinomial logistic regression analysis to investigate the determinants of selection decisions of M&A targets and acquirers in the US insurance industry.
Keywords: 330; Insurance industry; M&A acquirers; M&A targets; Mergers and acquisitions; Multinomial logistic regression analysis; US market